Linguocultural Aspect of the Content of Modern Foreing Language Textbooks - Григорьева, Елена (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The article deals with the design of school textbooks of a foreign language. The textbook is considered as the central link in the management of the educational process and one of the effective ways to optimize learning. The main functions of the textbook, the principles and requirements for its creation, features of the content and structure are highlighted. Teaching a foreign language is usually based on texts containing cultural history information. In the Russian linguodidactics of teaching foreign languages, the text is considered as a multifunctional educational unit. It is used at all stages of training and should have linguistic and linguoculturological potential.